Informasi akuntansi diferensial sebagai alat pengambilan keputusan investasi aset tetap: Studi kasus pada PT. Kuliner Dapur Om Buds - Chsili Oster Baradja; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2026)
Small and medium-sized enterprises (SMEs) in the food processing sector face critical fixed asset investment decisions affecting long-term financial sustainability, particularly when choosing between purchasing and leasing business facilities. This study analyzes the application of differential accounting information in fixed asset investment decision-making at PT. Kuliner Dapur Om Buds, a fish-processing enterprise in Manado, Indonesia, comparing purchasing and leasing a business building. Using a descriptive case study with quantitative financial analysis, data were collected through interviews, financial documents, and direct observation. Differential accounting information was combined with Payback Period (PP) and Net Present Value (NPV) analysis, applying a 12% discount rate over a five-year horizon. With average monthly revenue of IDR 250,000,000, results show leasing yields a higher differential profit of IDR 1,460,000,000 per year than purchasing (IDR 900,000,000). The Payback Period for purchasing is 26.7 months, while leasing recovers its outlay within one month. NPV for leasing reaches IDR 5,243,188,000, versus IDR 1,244,320,000 for purchasing. Both alternatives are financially feasible, but leasing performs better overall, offering practical guidance for similar SMEs.